Prognostic role of MIR146A polymorphisms for cardiovascular events in atrial fibrillation - Roldán, Vanessa; Arroyo, Ana Belen; Salloum-Asfar, Sallam; Manzano-Fernández, Sergio; García-Barberá, Nuria; Marín, Francisco; Vicente, Vicente; González-Conejero, Rocío; Martínez, Constantino (Thrombosis and Haemostasis, 2014)
There are few biomarkers able to forecast new thrombotic events in patients with AF. In this framework, microRNAs have emerged as critical players in cardiovascular biology. In particular, miR-146a-5p is recognised as an important negative regulator of inflammation. This study aims to evaluate the prognostic role and biological effect of functional MIR146A polymorphisms, rs2431697 and rs2910164, in non-valvular atrial fibrillation (AF) patients under oral anticoagulation. We studied 901 patients with permanent/paroxysmal AF stabilized for at least six months. Patients were followed-up for two years and adverse cardiovascular events (ACE) were recorded. In vitro studies were performed in monocytes from healthy homozygous for the two genotypes of rs2431697. Rs2910164 had no association with ACE. However, multivariate analysis (adjusted by CHA2DS2–VASc score) revealed that rs2431697TT was associated with adverse cardiovascular events [HR: 1.64 (1.09–2.47); p=0.017]. The predictive value of usefulness of the CHA2DS2–VASc+IL6+rs2431697 for predicting ACE, was statistically better than that predicted by CHA2DS2–VASc+IL6. Functional studies showed that after 24 hours incubation, monocytes from CC individuals showed a 65 % increase in miR-146a-5p levels, while TT individuals only showed a 28 % increase. Indeed, after 24 hours of LPS activation, TT monocytes showed a higher increase in IL6 mRNA expression than CC (52 % vs 26 %). Our study established MIR146A rs2431697 as a prognostic biomarker for ACE in anticoagulated AF patients. These data suggest that TT individuals, when submitted to an inflammatory stress, may be prone to a highest pro-inflammatory state due, in part, to lower levels of miR-146a-5p.
Keywords: Atrial fibrillation; mir-146a-5p; inflammation; cardiovascular event